Health Education 2.0: The Next Generation of Health Education Practice. (October 2013) - Fielding, Jonathan E.
Social, physical, and economic environments are the greatest determinants of our individual and collective health. Inadequate or substandard environments of all types present barriers to health. Addressing these broader determinants will be the quintessential core in the next era of public health practice. The framework for health improvement is shifting to a robust and comprehensive ecological model, wherein the broader constructs of health determinants will be central issues in population health improvement practice requiring expanded partnerships, increased application of scientific evidence, and healthy policy development within and outside of the traditional health sector. Health educators are uniquely positioned to effectively engage essential partners, shape information for policy makers, leverage the evidence base to implement effective interventions and maximize beneficial health outcomes, and add to the evidence base with thorough and systematic evaluation and reporting.